Menopause(s). Symbologies and cultural symptomatologies - García, Eva Margarita (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
For every women, the fertile period is closed with the arrival of the menopause,which can bring some physical, psychological and social alterations. On the following pages we are going to approach to the menopause transition with the purpose of understanding, first, if the symptoms that are traditionally linked to menopause are purely biological (and therefore, equal regardless of the culture) and, second, why in western societies there is an excessive medicalization in every moment of female sexuality (although we could say that the excessive medicalisation process belongs to western societies, it isn’t in the same way in women and men: women are medicated to run away from their nature, men are medicated to improve their nature). We will highlight how the status associated with the menopause is different in western cultures (where climacterium is unavoidably bind to the fear of aging) and how the excess of medicalization can be understood as an escape from this new period, in order to try to articially extend a normative youth. However, this doesn’t tend to happen in other cultures, where the social status completely improves when the menstrual period is missing, which has brought some authors to declare that the menopause concept is a western invention.